2014
DOI: 10.1093/molbev/msu135
|View full text |Cite
|
Sign up to set email alerts
|

How the Mountain Pine Beetle (Dendroctonus ponderosae) Breached the Canadian Rocky Mountains

Abstract: The mountain pine beetle (MPB; Dendroctonus ponderosae Hopkins), a major pine forest pest native to western North America, has extended its range north and eastward during an ongoing outbreak. Determining how the MPB has expanded its range to breach putative barriers, whether physical (nonforested prairie and high elevation of the Rocky Mountains) or climatic (extreme continental climate where temperatures can be below −40 °C), may contribute to our general understanding of range changes as well as management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 71 publications
10
108
0
Order By: Relevance
“…() and Janes et al. () found that Whistler was genetically different from other Canadian populations, but each provided slightly different explanations for the pattern. Janes et al.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…() and Janes et al. () found that Whistler was genetically different from other Canadian populations, but each provided slightly different explanations for the pattern. Janes et al.…”
Section: Discussionmentioning
confidence: 97%
“…Janes et al. () then surveyed variation in SNPs that were mainly selected for their potential functional role in MPB biology, confirming the north–south structuring of MPB populations in western Canada. This study suggested that multiple source populations contributed to the northern expansion and attributed the successful expansion to several outlier loci associated with cellular or metabolic functions.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations